Comparison of prognostic scores in transplant-ineligible patients with peripheral T-cell lymphoma not otherwise specified and angioimmunoblastic T-cell lymphoma: a retrospective study from the national hospital organization in Japan. Issue 4 (21st March 2021) - Yamasaki, Satoshi; Iida, Hiroatsu; Yoshida, Isao; Komeno, Takuya; Sawamura, Morio; Matsumoto, Morio; Sekiguchi, Naoshiro; Hishita, Terutoshi; Sunami, Kazutaka; Shimomura, Takeshi; Takatsuki, Hiroshi; Yoshida, Shinichiro; et al.
Abstract: We retrospectively analyzed the risk factors for outcomes among patients with peripheral T-cell lymphoma not otherwise specified (PTCL-NOS, n  = 100) and angioimmunoblastic T-cell lymphoma (AITL, n  = 128) who did not receive hematopoietic stem cell transplantation between 2008 and 2018. We designed a comparison of prognostic scores specifically for PTCL-NOS and AITL. The international prognostic index (IPI) was useful for investigating the risk factors associated with outcomes among transplant-ineligible patients with PTCL-NOS (Harrell's c-statistic 0.715) and AITL (c-statistic 0.615). The prognostic index for T-cell lymphoma (PIT), modified PIT, and the International Peripheral T Cell Lymphoma Project for overall survival (OS) seemed to identify separate prognostic groups, based on visual assessment of Kaplan–Meier curves. However, better c-statistics (>0.7) were only found for the IPI score for OS in PTCL-NOS. Strategies that carefully select PTCL patients with higher IPI scores may help to identify individuals suitable for novel therapies.